2021
DOI: 10.1158/1078-0432.ccr-21-0161
|View full text |Cite
|
Sign up to set email alerts
|

Kinobead Profiling Reveals Reprogramming of BCR Signaling in Response to Therapy within Primary CLL Cells

Abstract: Running title: Therapy induces adaptive signaling changes in primary CLL.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…To understand how BCR signaling is affected by mutations such as BTK L528W that impair kinase function, we next used a kinobead/mass spectrometry–based protocol to systematically evaluate the abundance of kinases and their active site availability in BTK WT and mutant TMD8 cells. Recently, this approach was successfully used to probe BCR signaling in CLL cells ( 32 ) and was performed here with and without IgM stimulation and in the presence or absence of pirtobrutinib treatment (fig. S1G).…”
Section: Drug Resistance Mutations In Btk Have Distinct Enzymatic Act...mentioning
confidence: 99%
“…To understand how BCR signaling is affected by mutations such as BTK L528W that impair kinase function, we next used a kinobead/mass spectrometry–based protocol to systematically evaluate the abundance of kinases and their active site availability in BTK WT and mutant TMD8 cells. Recently, this approach was successfully used to probe BCR signaling in CLL cells ( 32 ) and was performed here with and without IgM stimulation and in the presence or absence of pirtobrutinib treatment (fig. S1G).…”
Section: Drug Resistance Mutations In Btk Have Distinct Enzymatic Act...mentioning
confidence: 99%
“…This study revealed that the signature of isolated kinases in CLL cells from pre‐treatment patients is significantly different from patients receiving chemoimmunotherapy and ibrutinib treatment and that individual patients also showed signalling heterogeneity in response to the therapy [85]. It was also found that the CLL cells from ibrutinib‐treated patients undergo active rewiring of BCR signalling with significant increase activation of SYK, FAK2, GAK and RSK2 [85]. This study hence demonstrates that the kinobeads approach could provide insights into the potential drivers of signal pathway reprogramming in response to the therapy that may inform further treatment options.…”
Section: Applications Of Mass Spectrometry‐based Proteomics To Study ...mentioning
confidence: 99%
“…Recently, Linley et al [85] applied a kinobeads‐based approach to study the adaptive response of the B‐cell receptor (BCR) signalling in primary CLL cells following exposure to ibrutinib. This study revealed that the signature of isolated kinases in CLL cells from pre‐treatment patients is significantly different from patients receiving chemoimmunotherapy and ibrutinib treatment and that individual patients also showed signalling heterogeneity in response to the therapy [85]. It was also found that the CLL cells from ibrutinib‐treated patients undergo active rewiring of BCR signalling with significant increase activation of SYK, FAK2, GAK and RSK2 [85].…”
Section: Applications Of Mass Spectrometry‐based Proteomics To Study ...mentioning
confidence: 99%